Significance of asymmetrically inverted T wave. Issue 6 (June 1983) - Short, D; Weir, J
Abstract : Two consecutive series of patients with a T wave asymmetry ratio of 2.0 or greater have been studied. Patients with bundle-branch block or who were on digoxin or a similar drug were excluded. In 50 of the 69 patients, the heart was examined either by echocardiography or by direct inspection. Sixty-one of the 69 patients had diseases commonly associated with left (or right) ventricular hypertrophy and/or dilatation. The remaining eight patients had clinically pure ischaemic heart disease. Of the 50 hearts examined by echocardiography or direct inspection (including six with pure ischaemic heart disease), 49 were found to have abnormal thickness of the left (or right) ventricle, or increased end-diastolic left ventricular diameter, or a combination of hypertrophy and dilatation. In 12 of the 47 patients with left ventricular hypertrophy or dilatation, the electrocardiogram did not satisfy the Sokolow and Lyon voltage criterion of left ventricular hypertrophy.